THE ACCURACY OF AN ACCELERATED METHOD FOR THE EVALUATION OF LIFE OF CYLINDRICAL GEARS WITH PROFILE CORRECTION - Myron CZERNIEC (Applied Computer Science, 2015)
This paper presents an accelerated method for the evaluation of life of cylindrical gears with profile correction. Compared to a more accurate solution based on the generalized method for evaluating the wear and life of cylindrical involute gears, the new method enables accelerating this process by over 16000 times. The method was used to estimate the life of a cylindrical spur gear depending on different ranges of blocks describing gear teeth meshing conditions (i.e. the number of gear revolu-tions). The accuracy of the results obtained thereby was examined, too. It has been found that when the range of a block is increased by 3000 times, the deviations of the numerical solution are below 0.5%.